Catheter-related thrombosis natural history in adult patients: a tale of controversies, misconceptions, and fears. Issue 4 (July 2020) - Pinelli, Fulvio; Balsorano, Paolo
Catheter-related thrombosis natural history understanding might play a pivotal role in the way we approach to symptomatic and asymptomatic events. At the moment, little is known about catheter-related thrombosis natural history in adult patients, where the fear for embolic events and thrombus extension often leads to a precautionary behavior as for screening and management. In adult population, the knowledge of the natural history of symptomatic and asymptomatic catheter-related thromboses can only be indirectly inferred by studies designed for other purposes. From the available evidence on symptomatic patients, it can be assumed that the majority of catheter-related thromboses are early-onset events, where the endothelial damage during vein puncture might play a significant role in their development. Furthermore, symptomatic thrombotic events seem to have a low potential for major complications following treatment. On the contrary, catheter-related thrombosis natural history is more controversial in asymptomatic patients due to the lack of studies in this setting. At the moment, we can only make assumptions from studies in the pediatric population, where asymptomatic events appear to have a low potential for acute embolism and long-term sequelae when no treatment is established.